Enhancing Digital Health Literacy to Improve Quality of Life: Evidence Based Strategies for Public Health Advancement - Yani, Ahmad; Nirwan, Multy; Umar, Fadly; Afriyanto, Indra (Yayasan Sinergi Kawula Muda, 2022)
The increasing reliance on digital health interventions has underscored the need to enhance digital health literacy to improve individual health outcomes and quality of life. This study explores the effectiveness of digital health literacy interventions, including mobile applications, online education platforms, and telehealth services, in improving health knowledge and self-care behaviors. A systematic literature review was conducted using databases such as PubMed, Scopus, and Google Scholar, with selected studies focusing on adult populations and chronic disease management. Findings indicate that digital interventions significantly enhance health literacy and health-related behaviors; however, challenges such as disparities in digital access, socioeconomic factors, and variations in digital literacy levels limit widespread adoption. Comparative analysis reveals that while digital interventions offer advantages in accessibility and engagement, they must be adapted to different demographic and socioeconomic contexts to ensure equity. Policy implications highlight the necessity of investing in digital infrastructure, integrating digital literacy into healthcare education, and implementing data security regulations to foster trust and usability. The study concludes that digital health literacy is a crucial component of modern healthcare strategies. Addressing barriers and optimizing digital intervention designs are essential for maximizing the potential of digital health tools in promoting preventive care and improving public health outcomes. Future research should focus on long-term intervention effectiveness, AI-driven personalization, and culturally inclusive health literacy programs.